2018
DOI: 10.1177/1556264618820219
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ethical Concerns About Human Challenge Studies: A Qualitative Study of Controlled Human Malaria Infection Study Participants’ Motivations and Attitudes

Abstract: Controlled human malaria infection (CHMI) studies deliberately infect healthy participants with malaria to test interventions faster and more efficiently. Some argue the study design and high payments offered raise ethical concerns about participants' understanding of risks and undue inducement. We conducted baseline and exit interviews with 16 CHMI study participants to explore these concerns. Participants described themes including decision-making tension with friends and family, mixed motivations for partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…Research into the attitudes of CHIM participants has found that the physical requirements of participation can be 'more significant or more painful than expected'. 59 This may indicate that more effort is needed to both accurately describe the expected level of pain in a CHIM and to provide adequate compensation for the pain. However, the elusive and subjective nature of pain makes it extremely difficult to accurately quantify, describe and hence determine payment for.…”
Section: Augmentation For Risk and Painmentioning
confidence: 99%
“…Research into the attitudes of CHIM participants has found that the physical requirements of participation can be 'more significant or more painful than expected'. 59 This may indicate that more effort is needed to both accurately describe the expected level of pain in a CHIM and to provide adequate compensation for the pain. However, the elusive and subjective nature of pain makes it extremely difficult to accurately quantify, describe and hence determine payment for.…”
Section: Augmentation For Risk and Painmentioning
confidence: 99%
“…Research participation can involve a range of burdens; and some HCS designs entail relatively high levels of burdens for participants (eg, studies involving higher risk pathogens and/ or long periods of inpatient isolation and/or close monitoring of participants), especially in comparison with other studies involving healthy volunteers. 32 Here, we use 'burdens' to capture all potential compromises of individuals' interests that occur due to research participation, including exposure to risk, privacy infringements, restrictions of freedom of movement, loss of time, other reductions in well-being, etc. 33 The following sections summarise the findings of our project regarding (i) upper limits to risks to participants in HCS in general, (ii) risks to participants in (LMIC) HCS in particular, (iii) other burdens of participation, (iv) the right to withdraw and (v) risks to third parties.…”
Section: Risks and Other Burdensmentioning
confidence: 99%
“…Participants from both countries, however, showed little concern about trial risks and showed high levels of trust in the study team. In a qualitative study among US CHMI participants, 17 the participants similarly describe little concerns about the risks, trust in the study team as important and mixed motivations for participation. The differences between the American, Kenyan and Dutch CHI participants illustrate the influence of cultural differences and healthcare organisation that remain important to address and separately investigate.…”
Section: Open Accessmentioning
confidence: 99%